A five-year survey of onychomycosis in New Delhi, India: Epidemiological and laboratory aspects - Kaur Ravinder; Kashyap Bineeta; Bhalla Preena (Wolters Kluwer Medknow Publications, 2007)
Context: The worldwide incidence of onychomycosis is increasing and it continues to spread and persist. Knowledge of the epidemiological and mycological characteristics is an important tool for control of this infection. Aims: This study seeks to improve knowledge of onychomycosis epidemiology and mycological features. Settings and Design: Over a period of five years (Jan 2000 - Dec 2005) samples from 400 patients with clinical suspected fungal nail infections, who attended dermatology out patient department at a tertiary care hospital, were obtained. Materials and Methods: 400 nail specimens of suspected onychomycosis were evaluated clinically, KOH examination and fungal culture was done. Results: Onychomycosis was present in 218 (54.5%) by culture and /or direct examination. Fingernails and toenails were infected in 65% and 32% respectively and remaining 3% had both. Conclusions: This study demonstrated that dermatophytes were main agents causing onychomycosis in our region, as well as the importance of performing direct examination and culture in diagnosis of onychomycosis.